2015
DOI: 10.1038/ncomms8052
|View full text |Cite
|
Sign up to set email alerts
|

JMJD1A is a signal-sensing scaffold that regulates acute chromatin dynamics via SWI/SNF association for thermogenesis

Abstract: Histone 3 lysine 9 (H3K9) demethylase JMJD1A regulates β-adrenergic-induced systemic metabolism and body weight control. Here we show that JMJD1A is phosphorylated at S265 by protein kinase A (PKA), and this is pivotal to activate the β1-adrenergic receptor gene (Adrb1) and downstream targets including Ucp1 in brown adipocytes (BATs). Phosphorylation of JMJD1A by PKA increases its interaction with the SWI/SNF nucleosome remodelling complex and DNA-bound PPARγ. This complex confers β-adrenergic-induced rapid JM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
212
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(226 citation statements)
references
References 44 publications
6
212
0
5
Order By: Relevance
“…In brown adipocytes, shRNA-mediated depletion of BRG1, a catalytic component of the BAF complex, dramatically reduced the expression of Ucp1 and other brown fat-specific genes, with no effect on general adipocyte genes (Supplemental Fig. S2A), as also reported by Abe et al (2015). This suggested that EBF2 may cooperate with BRG1 and the BAF complex to remodel the chromatin structure of brown fat gene enhancers.…”
Section: Ebf2 Interacts With Brg1 and The Baf Chromatin Remodeling Cosupporting
confidence: 57%
See 2 more Smart Citations
“…In brown adipocytes, shRNA-mediated depletion of BRG1, a catalytic component of the BAF complex, dramatically reduced the expression of Ucp1 and other brown fat-specific genes, with no effect on general adipocyte genes (Supplemental Fig. S2A), as also reported by Abe et al (2015). This suggested that EBF2 may cooperate with BRG1 and the BAF complex to remodel the chromatin structure of brown fat gene enhancers.…”
Section: Ebf2 Interacts With Brg1 and The Baf Chromatin Remodeling Cosupporting
confidence: 57%
“…ATP-dependent chromatin remodelers have dynamic and transient interactions with chromatin; therefore, binding events may be difficult to detect by ChIP assays. Previous work indicates that iso stimulates BRG1/BAF recruitment to brown fat-specific enhancers in mature brown adipocytes (Abe et al 2015) and thus provides a defined time frame to observe BRG1-binding dynamics. Consistent with this, we observed increased BRG1 recruitment to Ucp1 and Ppara after 3 h of iso treatment (Fig.…”
Section: Dpf3 Regulates Chromatin Structure At Brown Fat-specific Enhmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion is based on the observed differential outcomes of loss-of-function and gain-of-function KDM3A manipulations in TS cells and the absence of conserved HIF binding motifs in regulatory regions binding KDM3A. In addition to HIF, there is evidence for other types of transcription factors (e.g., nuclear receptors and OCT1) guiding KDM3A to its genomic targets in various nontrophoblast cells (51)(52)(53). Mechanisms controlling KDM3A arrival at its target loci within the TS cell genome are yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…PRC1, in turn, can ubiquitinate lysine 119 of histone H2A, leading to a closing of the chromatin structure [46,189]. Similarly, KDM3A and KDM6 demethylases play a role in chromatin remodeling by linking transcription factors with the SWI/SNF chromatin remodeling complex [190,191]. Since these proteins regulate the chromatin compaction associated with genes involved in carcinogenesis and cell proliferation, mutation or depletion of histone demethylases could interfere with these biological processes.…”
Section: Beyond the Histone Demethylase Functionmentioning
confidence: 99%